Development and validation of a rapid high performance liquid chromatography - photodiode array detection method for estimation of a bioactive compound wedelolactone in extracts of Eclipta alba - Satyanshu Kumar; Tushar Dhanani (Universidade de São Paulo, 2013)
Following optimization of extraction, separation and analytical conditions, a rapid, sensitive and simple reverse-phase high performance liquid chromatography-photo diode array (HPLC-PDA) method has been developed for the identification and quantification of wedelolactone in different extracts of Eclipta alba. The separation of wedelolactone was achieved on a C18 column using the solvent system consisting of a mixture of methanol: water: acetic acid (95: 5: 0.04) as a mobile phase in isocratic elution mode followed by photo diode array detection at 352 nm. The developed method was validated as per the guidelines of the International Conference on Harmonization (ICH). Calibration curve presented good linear regression (r²>0.998) within the test range and the maximum relative standard deviation (RSD, %) values for intra-day assay were found to be 0.15, 1.30 and 1.1 for low (5 µg/mL), medium (20 µg/mL) and high (80 µg/mL) concentrations of wedelolactone. For inter-day assay the maximum RSD (%) values were found to be 2.83, 1.51 and 2.06 for low, medium and high concentrations, respectively. Limit of detection (LOD) and limit of quantification (LOQ) were calculated to be 2 and 5 µg/mL respectively. Analytical recovery of wedelolactone was greater than 95%. Wedelolactone in different extracts of Eclipta alba was identified and quantified using the developed HPLC method. The validated HPLC method allowed precise quantitative analysis of wedelolactone in Eclipta. alba extracts. Desenvolveu-se método rápido, sensível e simples de Cromatografia Líquida de Alta Eficiência em fase reversa, utilizando-se arranjo de fotodiodo (HPLC-PDA), visando à separação, extração e às condições analíticas para a identificação e quantificação de wedelolactona em diferentes extratos de Eclipta alba. A separação de wedelolactona foi efetuada por meio de uma coluna C18, utilizando mistura de metanol:água:ácido acético (95:5:0.04) como fase móvel, em sistema de eluição isocrática, seguida de detecção por arranjo de fotodiodo a 352 nm. O método desenvolvido foi validado de acordo com as diretrizes da Conferência Internacional de Harmonização (ICH). As curvas de calibração apresentaram boa regressão linear (r²>0,998), dentro dos intervalos de teste, e os valores máximos de desvio padrão relativo (RSD,%) dos ensaios intra-dia foram 0,15, 1,30 e 1,1 para concentrações de wedelolactona baixa (5 µg/mL), média (20 µg/mL) e elevada (80 µg/mL) Para o ensaio inter-dia,os máximos de RSD (%) foram 2,83, 1,51 e 2,06 para as concentrações baixa, média e alta, respectivamente. O Limite de Detecção (LD) e o Limite de Quantificação (LOQ) foram de 2 e 5 µg/mL, respectivamente. A recuperação analítica de wedelolactona foi maior do que 95%. A wedelolactona em diferentes extratos de Eclipta alba foi identificada e quantificada pelo método de HPLC desenvolvido. O método de HPLC validado permitiu a análise quantitativa precisa de wedelolactona em extratos de Eclipta alba.